A priori design of new natural deep eutectic solvent for lutein recovery from microalgae. (15th May 2022) - Fan, Chen; Liu, Yang; Shan, Yuhang; Cao, Xueli
Graphical abstract: Highlights: COSMO-RS model was used to rationally design natural deep eutectic solvent (NADES). The NADES has an excellent lutein recovery ability from microalgal biomass. Different parameters including solvent systems, extraction time and temperature were optimized. The new fenchyl alcohol/thymol-based NADES improves the stability of lutein. Hydrogen bond and Van der Waals interaction play vital roles in recovery and stabilization. Abstract: Lutein is an important functional food ingredient. However, its recovery processes developed so far seem to fail in sustainability criteria, regarding the urgent need for improved extraction ability while maintaining stability. This work aimed to study the design and application of natural deep eutectic solvent (NADES) for lutein recovery from Scenedesmus sp with the aid of COSMO-RS. The performance of the novel fenchyl alcohol/thymol-based system was studied comprehensively under different extraction parameters. Furthermore, thermal, light and storage stability of lutein in NADES were investigated. It was found that lutein recovery from microalgae should be performed using equimolar hydrogen-bond acceptor/donor at 60 °C within 70 min. The NADES could increase lutein yield compared with the conventional methodology using organic solvents. Besides, it significantly enhanced the lutein stability under various conditions. Hydrogen bond and Van der Waals interaction play crucial roles during target processing, elucidated by theoretical calculations and nuclear magnetic resonance.